2011
DOI: 10.1016/j.joep.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Subject-specific performance information can worsen the tragedy of the commons: Experimental evidence

Abstract: The main aim of this article is to investigate the behavioral consequences of the provision of subject-specific information

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The participants' decisions might be influenced by their expectations of what others will do. In various previous studies, providing more information so that free-riding can be observed reduced cooperation (Nikiforakis 2010, Villena andZecchetto 2010). When we reduced the visibility of others, we expected this would take longer to detect free-riding behavior.…”
Section: Experimental Designmentioning
confidence: 81%
See 1 more Smart Citation
“…The participants' decisions might be influenced by their expectations of what others will do. In various previous studies, providing more information so that free-riding can be observed reduced cooperation (Nikiforakis 2010, Villena andZecchetto 2010). When we reduced the visibility of others, we expected this would take longer to detect free-riding behavior.…”
Section: Experimental Designmentioning
confidence: 81%
“…When more information about the actions of others is available to participants, we see lower levels of cooperation in most studies, since more details reveal the existence of free riders (Nikiforakis 2010, Villena andZecchetto 2010). When the information is focused on the intentions of conditional cooperators in the group, we see that more information leads to higher levels of cooperation (Chaudhuri andPaichayontvijit 2006, de Oliveira et al 2009).…”
Section: Past Experiments On Common Pool Resourcesmentioning
confidence: 90%
“…This enables us to look at fundamental drivers of decision making in typical conditions that many small scale irrigation communities face. Results from earlier social dilemma -not irrigation dilemma -experiments suggest that limiting the information will affect the experimental outcomes [12,13,14]. Since the majority of participants act in experiments as if they are conditional cooperators, information availability affects the expectations participants have and therefore their tendency to cooperate [15].…”
Section: Introductionmentioning
confidence: 99%
“…Observed discrepancies between one's own and the group's behavior could lead to a shift in subjective transformation functions. This would go beyond the mere imitation of successful others (Apesteguia, Huck, & Oechssler, 2007;Burton-Chellew & West, 2013;Garcia-Ratamero, Takezawa, Woike, & Gigerenzer, 2013;Villena & Zecchetto, 2011). Such future research might further examine to which degree the observation of conditional cooperation (Charness & Rabin, 2002;Fischbacher et al, 2001;Fischbacher & Gächter, 2010) can be explained by a re-interpretation of the interdependence structure and how feedback impacts those with strong and weak tendencies to reciprocate.…”
Section: Limitations and Future Researchmentioning
confidence: 99%